Pengembangan Sound Card Laptop sebagai Alat Praktikum Fisika untuk Penentuan Percepatan Gravitasi Bumi - Eka Maryam; Ahmad Fahrudin (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this research is to develop a laptop soundcard as a physics practice tool for the determination of Earth grafitational acceleration. The Earth's gravitational force is the power that makes the Earth draw objects to its center. This tool is designed using 3 pieces of copper coil separated by a certain distance. The Data obtained is presented in the form of Time (t) which is calculated from the symptoms of induction by magnetic through the coil. When the magnet is dropped, time is measured from the emergence of pulse when the magnet induces the coil using the Audacity software. From the Pulse brings out the results of time in each distance. This research uses development methods with Analysis, Design, Development, Implementation, Evaluation (ADDIE). The laptop's practicum soundcard tool is validated by expert tools for technical aspects and students as a test user. Data collection techniques in this research using poll. Angket is used to measure the feasibility of the development of laptop soundcard equipment. The poll is given to 3 members of the Practicum tools and students as a user. A poll validation analysis uses a Likert scale with a value range of 1 to 5. This results in a practical tool that has a good graphing perceptant measurement accuracy with a 2.33% error. While the result of validation shows that both validation provides excellent responsiveness so that, practicum soundcardlaptop tool can be used practicum.